Synthesis, characterization and evaluation of Pamam Dendrimer-Gold complex as an anion recognition material - Abd. Malek, Muhammad Nor Fazli (2009)
Dendrimers are highly branched, monodisperse macromolecules and this field of study has increased rapidly from the time they were discovered about twenty years ago. In this study, PAMAM dendrimer was successfully synthesized by a divergent synthesis route using the reagent excess method starting from ethylenediamine (EDA) followed by consecutive Michael addition and ester amidation reaction. Methanol was used as solvent and three dendrimer generations were prepared: G 1.0, G 2.0 and G 3.0. For preparation of PAMAM-thiol functionalized gold nanoparticle in-situ reduction of gold from Au 3+ to Au0 was achieved through the reaction of nanogold-thiol functionalized PAMAM dendrimer with sodium borohydrate (NaBH4). The PAMAM dendrimer-gold complex gave light purple solution and was characterized by *H nucleus magnetic resonance (NMR), Fourier transform infrared (FT-IR), and ultraviolet-visible (UV-Vis) spectroscopies. Analysis of the UV-Vis spectral analysis of the PAMAM dendrimers showed that the wavelength maximum, Xmax significantly shifted from 330.15 nm to 517.28 nm with the addition of goldthiol nanoparticles due to binding of the thiol functional group to gold particles. Anion recognition ability of the PAMAM-thiol functionalized gold nanoparticle has been studied by treating the PAMAM dendrimer-gold complex with nitrate ion. Based on the UV-Vis spectra, the wavelength maximum of Au(III) was shifted from 526.98 nm to higher wavelength upon binding of the nitrate anion to the surfaces of gold-thiol nanoparticles which the process involved excitation of the electrons from n -> n*.